INTERPRETATION OF THE CONCEPT OF "MOTHERLAND" IN THE POEMS AND GHAZALS OF ZAHIRIDDIN MUHAMMAD BABUR - Javliyev Mansurbek Odil o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
In the process of studying the concept of "Motherland", our great grandfather, king and poet, Zahiriddin Muhammad Babur who spent most of his life with a sense of longing for his country depicted the homeland with great skill and emigration. Speaking about our grandfather, it is worth emphasizing that he has an incomparable place in our history and literature. Especially, noteworthy thing is the poems of the poet, in which a new spirit is woven into our classic poetry - the glory of love for the Motherland. At this point, it is appropriate to quote the following opinions of literary scholar V. Rahmonov: “In terms of artistic skills, no Uzbek poet can compete with Babur, and the biographical feature that he boldly introduced into classical poetry also shines a special light on Babur’s poetry. This next feature gives life to the poet’s patriotic feelings”.